Living Donor Liver Transplantation for Patients with Hepatocellular Carcinoma - Akamatsu, Nobuhisa (S. Karger AG, 2014)
BACKGROUND: Liver transplantation has become an established treatment for cirrhotic patients with hepatocellular carcinoma (HCC), and the Milan criteria are now widely accepted and applied as an indication for deceased donor liver transplantation (DDLT) in Western countries. In contrast, however, due to the severe organ shortage, living donor liver transplantation (LDLT) is mainstream in Japan and in other Asian countries. SUMMARY: Unlike DDLT, LDLT is not limited by the restrictions imposed by the nationwide allocation system, and the indication for LDLT in patients with HCC often depends on institutional or case-by-case considerations, balancing the burden on the donor, the operative risk, and the overall survival benefit for the recipient. Accumulating data from a nationwide survey as well as individual center experience indicate that extending the Milan criteria is warranted. KEY MESSAGES: While the promotion of DDLT should be intensified in Japan and other Asian countries, LDLT will continue to be a mainstay for the treatment of HCC in cirrhotic patients.